Stability Analysis of a Laminated Composite Micro scaled beam embedded in elastic medium using modified coupled stress theory - Akbas, Seref Doguscan (Univ Tehran, Danishgah-I Tihran, 2024)
This paper presents size dependent stability analysis a cantilever micro laminated beam embedded in elastic medium by using the modified coupled stress theory which includes the length scale parameter. The micro beam subjected to compressive load is considered as three composite laminas and embedded in elastic medium which is modelled in the Winkler foundation model. In the obtaining of the governing equations, the energy principle is used. In the solution of the buckling problem, the energy based Ritz method is implemented with algebraic polynomials. In order to accuracy obtained expressions and used method, a comparative study is performed. Many parametric studies are presented in order to investigate the buckling of laminated micro beams. For this purpose, effects of stacking sequence of laminas, geometric parameters, length scale parameter, fiber orientation angle, the parameter of elastic medium on critical buckling loads of laminated micro beams are investigated.
Keywords: Micro Scaled Beam; Laminated Composites; Buckling; Elastic Medium; Modified Coupled Stress Theory